Argument Driven Inquiry-Based Students’ Worksheets on the Topics of Free Fall Movement to Improve Students’ Curiosity - Setiawan, Annisa; Nugroho, Ichwan Restu; Nurohman, Sabar; Jumadi, Jumadi (Jurnal Pendidikan Progresif, 2023)
Argument Driven Inquiry-Based Students’ Worksheets on the Topics of Free Fall Movement to Improve Students' Curiosity. This research is to determine validity, effectiveness, and practicality of an Argument-Driven Inquiry-based students’ worksheets development in an effort to increase students' curiosity. Development method used is 4D (Define, Design, Develop, and Disseminate). Development stage is carried out by developing and perfecting students’ worksheets products that can be applied in classroom learning. This stage validation was carried out by three validators consisting of 3 science teachers with results of each validator being valid and very valid. Practicality students’ worksheets was obtained from the score of response questionnaire and observation. The response questionnaire, a score of 90.72% was obtained, while from observation, a score of 90% was obtained. From the average results obtained a score 90.36% which is categorized as very practical. Based on this, it can be concluded that development Argument-Driven Inquiry-based free fall motion worksheets for learning obtains valid, effective, and practical categories in increasing student’s curiosity about Newton's law free fall. Keywords: students’ worksheets, argument driven inquiry, curiosity. DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202341